Germany : Selected Background Issues. (IMF Staff Country Reports; Country Report, 1995)
This Selected Background Issues paper examines the process of international financial integration in Germany, focusing on both banking and securities markets. The examination is useful both because of the size and importance of Germany's economy and because of the structure of its financial markets, which rely on bank-based finance as opposed to securities-based finance to a greater extent than most other major industrial countries. The paper examines the data demonstrating the increased internationalization of German financial markets. It also considers measures taken by authorities to facilitate the internationalization process.